The Call for a New Ecotheology in Norway - Anker, Peder (Journal for the Study of Religion, Nature and Culture, 2013)
The call for a new ecotheology in Norway began in the early 1970s with environmentally concerned deep ecologists and continued within the Evangelical Lutheran Church of Norway and the university system. Church officials and intellectuals saw ecotheology as an effective way of engaging the young in caring for the Creation. Alongside the eco-philosophical projects of redefining the natural, the deep ecologists also sought to renew religious faith. Norwegian theologians found their questioning of economic growth, technocracy, and industrialism appealing, and they sympathized with their call to save wilderness and their endorsement of outdoor life, rural communities, and modest lifestyles. Deep ecology represented for theologians an opportunity to revive the Church, mobilize a new and younger audience, and address the question of how to behave towards God’s Creation.